The effects of the activities of The United Nations Humanitarian Air Service (UNHAS) in humanitarian logistics in 2019-2022 - LANDMANN TOMASZ; Ślusarczyk Stanisław (2024)
The subject of the article are selected results of the activities of The United Nations Humanitarian Air Service (UNHAS) as a service of the United Nations carrying out air operations for humanitarian purposes. The article adopts a research goal of explaining the specialization and effects of UNHAS activities in humanitarian logistics in 2019-2022. The research problem in the work is as follows: What were the results of UNHAS activities in humanitarian logistics in 2019-2022? The research hypothesis in the article is as follows: UNHAS effectively implemented international humanitarian aid in 2019-2022, serving United Nations agencies and non-governmental organizations in particular. UNHAS activities included such trends as the increase in the number of passengers transported from crisis areas and goods for humanitarian purposes, the increase in the number of destinations for providing humanitarian aid and the increase in the value of financing humanitarian operations. The main sources of problems and challenges in the functioning of UNHAS in 2019-2022 are the difficulties in forecasting the scale of humanitarian needs and the growing financial gap and dependence on the political will of the United States and the state of cooperation between that country and OCHA as a UN body and additionally the European Union. For the purposes of the article, research methods were used in the form of analysis of existing data (desk research), analysis of documents published by WFP as the organization managing UNHAS activities, as well as a case study for UNHAS as a specialized humanitarian aid support service in the UN institutional system. The article shows that UNHAS is the UN humanitarian service specializing in the implementation of air operations for humanitarian purposes. From 2019 to 2022, most of UNHAS's efforts focused on delivering humanitarian aid to African countries. The Covid-19 pandemic temporarily weakened the capabilities of humanitarian operations, which, combined with the financial gap, amplified the challenges in humanitarian logistics at the turn of the second and third decades of the 21st century.